RETRACTED: Effectiveness of physical qualities development in elementary school students - Ma’murov Bahodir; Davronov Nurzod; Qo’ldoshev Rustambek; Usmonov Zufar; Saidov G’olibjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001